PEMANFAATAN FITUR & PRAKTIK TERBAIK SOCIAL MEDIA TERHADAP E-COMMERCE - Wiwik Rachmarwi (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
This study aims to examine the use of features and best practices of social media on the Enhancement of E-Commerce, especially Instagram, which can support current trends in online purchasing. In this research is descriptive quantitative. The number of samples used using simple random sampling. The results of this study provide results on Instagram best features and practices that can contribute greatly to the digital economy, e-commerce. Instagram is the perfect social media platform for running an online business, because Instagram has functional features in displaying products, connecting with target customers, and developing broader discussions that make their brands able to offer their ideal customers and by implementing best practices can encourage consumer engagement